Human Trafficking and Migration: An Exploration of the Spanish Protection System from a Comparative Perspective - Miranda Ruche, Xavier; Villacampa Estiarte, Carolina (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
Spain has a large number of migrants among victims of human trafficking. Thus, this article provides a critical approach to the Spanish protection system aimed at such victims. A comparative analysis with five European countries was performed to this end. The results show that Spain has a poor infrastructure to conduct the identification process. As a result, undetected victims are prevented from accessing formal protection coverage and access to the recovery and reflection period, as well as a residence permit, is blocked. To ensure victims’ rights and assistance, Spain should articulate an identification system made up of a more significant number of specialised agents, as seen in the British, Portuguese and Dutch model. Given the high migration component of human trafficking, such system should be particularly qualified in cultural diversity.